Analysis and Characterization of Fe3O4/Silica Composite from Rice Husk Ash - Susilawati Susilawati; Hariyati Lubis; Jeddah Yanti; Syahrani Nabilla Pardede; Agnes Federova Napitupulu (Journal of Technomaterial Physics, 2024)
In this investigation, Fe3O4/Silica composites were synthesized from rice husk ash utilizing the coprecipitation technique, aiming to elucidate the influence of variedheating temperatures on the surface morphology and elemental composition of the composites. Comprehensive characterizations were conducted employing FourierTransform Infrared (FTIR) Spectroscopy, X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM). These analyses unveiled a heterogeneous distributionof Fe3O4 nanoparticles and affirmed the amorphous characteristic of the silica constituent, with the XRD results prominently displaying a broad peak at approximately 2Î¸ = 38°, signifying the amorphous nature. Despite the alterations in heating temperatures, SEM observations indicated a negligible effect on the nanoparticles' surface morphology, whereas notable variations were discerned intheir elemental composition. The outcomes of this study provide insightful contributions to the understanding of the structural properties of Fe3O4/Silica composites, suggesting avenues for refining synthesis methodologies for enhanced environmental and technological utilization.